Assessment of Parental Understanding of Positive Newborn Screening Results and Carrier Status for Cystic Fibrosis with the use of a Short Educational Video. Issue 3 (19th September 2014) - Temme, R.; Gruber, A.; Johnson, M.; Read, L.; Lu, Y.; McNamara, J.
Abstract: Many children are identified as unaffected carriers for cystic fibrosis (CF) through newborn screening (NBS) programs. The aim of this study was to improve parental understanding of positive NBS results using an educational video in addition to genetic counseling. One hundred parents of infants identified as CF carriers through NBS were randomly assigned by household to either a genetic counseling only group or a genetic counseling and video group. All participants completed a knowledge‐based questionnaire before, immediately after, and six weeks following genetic counseling. This included questions about resources accessed before and after the appointment. Seventy‐two percent of participants accessed resources on their own prior to genetic counseling; these participants scored significantly higher on the pre‐counseling questionnaire ( p  = 0.03). Post‐counseling knowledge scores for both groups significantly improved after genetic counseling ( p  < 0.001). Post‐counseling scores were significantly higher in the video group compared to the non‐video group ( p  = 0.02). Knowledge was retained six weeks following genetic counseling. This study demonstrates the effectiveness of an educational video and reinforces the importance of genetic counseling following positive NBS results for CF.